Behaviour Of Under-Reinforced Shallow Fibrous Concrete Beams Subjected To Pure Torsion - Karim, Ferhad Rahim (2016)
Torsional resistance of under-reinforced shallow fibrous concrete beams with the influence of the idealized core zone, thickness of concrete cover, bond strength and reinforcement indexes were investigated. Up-to-date, the contribution of the idealized core zone area and thickness of concrete cover to resist torsion based on thin-walled tube, space truss analogy have been ignored. In this investigation, thirty samples (30) of under-reinforced shallow fibrous concrete beams were prepared and tested under pure torsion. As a result, the torsional resistance of peak load was improved due to additional reinforcements in the idealized core zone area of the section, enhancement of bond strength between longitudinal reinforcement and fibrous concrete matrix, and reduction in the reinforcement indexes. Meanwhile, the torsional resistance at the crack and peak loads were improved due to thickening of concrete cover. Although the strain in longitudinal reinforcement was effected on crack number in fibrous concrete beams at failure, the reinforcement indexes and their bond strength in fibrous concrete were found to influence on the inclination angle of the crack at failure. The dimensional analysis and space truss model based on the established models were modified to propose a new approach for proving the effect of additional reinforcements in the idealized core zone, thickness of concrete cover and bond strength of embedded reinforcement in fibrous concrete on the torsional capacity of the beam. In conclusion, this study has proven the contribution of all the above mentioned parameters and the proposed equations for predicting torsional resistance at crack and-peak-loads are reasonably agreed with the results.